Silent Voices and Invisible Bruises-Unreported Abuse against the Senior Citizen: Addressing the Challenges of Elder Abuse and Neglect in Society (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The growing number of old age homes and cases of reported and unreported abuse against parents at the hands of their children and relatives is a cause of serious concern for any society. While the Government and the laws provides for means to protect the rights of senior citizens in India and several NGOs working to help the senior citizens , the legal machinery has a long way to go before we can actually provide some relief to this section of our population. The very use of word “May” instead of “shall” by our law makers while drafting Bills, or putting the rights of senior citizens under the Directive Principles of the Constitution, neither the State nor the Centre makes most of the provisions enforceable under law. Need of the hour is more stringent laws and a stronger society with values that teach us to take care of our elders and learn from their vast reservoir of knowledge and experience. The youth today must not forget that they will be senior citizens tomorrow.